(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In this article, methods of analyzing language structure are studied. In linguistics, the analysis of language structure requires various methodological approaches, including methods of syntactic, semantic, morphological, and pragmatic analysis. The article covers the theoretical foundations of these methods, their advantages, and areas of application. Corpus analysis, transformational and distribution methods used in modern linguistic research are also discussed. The research results demonstrate the importance of scientific approaches in the in-depth analysis of language structure and reveal their place in linguistic research.